Influence of prebiotics, probiotics and protein ingredients on mycotoxin bioaccessibility. Issue 3 (11th March 2015) - Ferrer, M.; Manyes, L.; Mañes, J.; Meca, G.
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the influence of prebiotic compounds (cellulose and inulin), food ingredients (milk whey, β-lactoglobulin and calcium caseinate) and several probiotic microorganisms on the bioaccessibility of beauvericin (BEA), enniatins (ENs A, A1, B, B1), deoxynivalenol (DON) and zearalenone (ZEA) present in wheat crispy bread produced with wheat flour previously fermented with F. tricinctum, F. culmorum and G. zeae.